Teaching English to Young Learners in Indonesia (Pros and Cons) - Tatu Zakiyatun Nufus (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2018)
Teaching English for young learners in Indonesia still invites the controversies among the educators and psycholinguists that concern on learners’ development in thinking and communication. Because teaching English for young learners in Indonesia seems to force them in knowing the rule and forms of the sentence. In addition, some of the teachers who teach English for young learners have not the appropriate educational background that can teach the younger as well as the objective wish. Actually, there is not any regulation or decisions that obligate the school to teach English to young learners. It only depends on the school itself. In this paper, the writer would like to describe the teaching English to young learners in Indonesia in the side of its implementation and also the pros and cons based on the second language acquisition experts.